2002
DOI: 10.1099/00221287-148-7-2065
|View full text |Cite
|
Sign up to set email alerts
|

Pattern searches for the identification of putative lipoprotein genes in Gram-positive bacterial genomes

Abstract: INTRODUCTIONThe bacterial cell envelope is of major significance as the focal point for interaction between the bacterium and its environment, notably the host in the case of bacterial pathogens. Bacterial cell envelope proteins thus carry out numerous important functions including roles in adhesion, nutrient acquisition and a variety of interactions with host defences. In Gram-positive bacteria the matrix of peptidoglycan and other wall polymers surrounding the cell is not an efficient barrier to the passage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
194
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 152 publications
(205 citation statements)
references
References 92 publications
8
194
0
1
Order By: Relevance
“…Moreover, genome analyses have consistently identified putative lipoproteins predicted to have important roles in cell envelope stability and cell wall cross-linking or remodelling such as penicillin binding proteins and peptidoglycan hydrolases [18,54]. For example, ErfK domain (PFAM PF03734) L,D transpeptidases were recently discovered to have roles in the alternative 3-3 cross-linking of peptidoglycan in Enterococcus faecium and M. tuberculosis [72,73], perhaps as a way of recycling or remodelling the peptidoglycan.…”
Section: Bioinformatic Prediction Of Lipoproteins In Grampositive Bacmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, genome analyses have consistently identified putative lipoproteins predicted to have important roles in cell envelope stability and cell wall cross-linking or remodelling such as penicillin binding proteins and peptidoglycan hydrolases [18,54]. For example, ErfK domain (PFAM PF03734) L,D transpeptidases were recently discovered to have roles in the alternative 3-3 cross-linking of peptidoglycan in Enterococcus faecium and M. tuberculosis [72,73], perhaps as a way of recycling or remodelling the peptidoglycan.…”
Section: Bioinformatic Prediction Of Lipoproteins In Grampositive Bacmentioning
confidence: 99%
“…Lipoprotein functions in Gram-positive bacteria Bioinformatic analyses (as described earlier) have indicated that lipoproteins are a relatively abundant family of proteins, typically representing 2% or more of a Grampositive bacterial proteome [18,19,43,54,57]. Functional analyses have revealed several recognisable functional groupings of Gram-positive bacterial lipoproteins [3], with these functions reflecting the localisation of lipoproteins within the cell envelope and more specifically at the interface between the membrane and the cell wall (Box 3).…”
Section: Bioinformatic Prediction Of Lipoproteins In Grampositive Bacmentioning
confidence: 99%
See 3 more Smart Citations